Does self-concept affect mathematics learning achievement? - Nia Kania; Dadang Juandi (Journal of Education and Learning (EduLearn), 2023)
Students who study at home certainly affect their self-concept. Their study found that knowledge of distance learning affects the perceived usefulness of this process. This study described self-concept has an influence on learning achievement in mathematics. The type of research used in this study was descriptive quantitative research to determine the relationship between students’ self-concept and learning achievement in mathematics. This research was conducted in class 8 of State Junior High School (SMPN) 1 Palasah, Indonesia with 151 students as respondents. The self-concept data was obtained from a study questionnaire that had previously estimated its validity and reliability. This analysis is used to explain the data in the form of standard deviation, average, and low score. Self-concept is categorized into three categories (high, medium, and low). Self-concept is categorized into two kinds, namely positive self-concept, and negative self-concept. Categorization of self-concept can also be divided into three kinds. A high self-concept is also called a more positive self-concept, a moderate self-concept is also called a positive self-concept, and a low self-concept is also called a negative self-concept. Therefore, when students have a positive self-concept, it affects learning achievement positively as students needhaveaves to have a self-concept in learning mathematics.